SETAHUN PANDEMI COVID-19 DAN DAMPAKNYA TERHADAP INDUSTRI PARIWISATA INDONESIA - Salman Paludi (Universitas Kuningan, 2022)
AbstractCoronaVirus Disease-2019 (Covid-19), a newcomer who has successfully terrorized mankind around the world since the last year. One of the government's efforts to break the chain of spreading this virus is by adopting social distancing and physical distancing policies and continuing with the policy of large-scale social restrictions for the Indonesian people. As a result, the number of foreign tourist visits to Indonesia has decreased sharply and the prohibition of tourism activities has caused the Indonesian tourism industry to experience a significant decline. By analyzing tourism statistics from the Central Bureau of Statistics of Indonesia, it is known that the number of foreign tourist arrivals through air entrances has decreased sharply where Ngurah Rai airport is the most affected, the occupancy rate of star hotels in Indonesia has decreased sharply, where hotels in Bali are the most affected, tens of millions of workers in the tourism sector are threatened with losing their jobs and national income from the tourism sector has decreased.Keywords: impact; Covid-19; foreign tourists; tourism. AbstrakCoronaVirus Disease-2019 (Covid-19), mahluk pendatang baru yang suskses meneror umat manusia di seluruh dunia sejak setahun terakhir. Salah satu upaya pemerintah untuk memutus mata rantai penyebaran virus ini adalah dengan mengambil kebijakan social distancing dan physical distancing dan dilanjutkan dengan kebijakan Pembatasan Sosial Berskala Besar bagi masyarakat Indonesia. Akibatnya jumlah kunjungan wisman ke Indonesia menurun tajam dan pelarangan aktivitas pariwisata menyebabkan industri pariwisata Indoneisa mengalami penurunan yang signifikan .Dengan menganalisa data statistik pariwista yang bersumber dari Badan Pusat Statistik diketahui bahwa, jumlah kedatangan wisman melalui pintu masuk udara menurun tajam dimana bandara Ngurah Rai yang paling terdampak, tingkat hunian hotel-hotel berbintang di Indonesia menurun tajam dimana hotel-hotel di Bali yang paling terdampak, belasan juta pekerja di sektor pariwisata terancam kehilangan pekerjaan dan pendapan nasional dari sektor pariwisata menurun.Kata kunci : dampak; Covid-19; wisman; pariwisata.